A reestruturação produtiva do capital e os rearranjos do trabalho no território fabril: um estudo sobre os trabalhadores da Fosfertil em Catalão-GO - Sussumo, Viviane Pimentel Moscardini (2009)
The present research begins with na geographical about the reestruturation in course on the world of work, mainly in the last decades, in the moment that the capital get more flexible ways of reprodution. We try to investigate how these changes territorial in the plant space of Fosfertil and the consequences to the works (employers). This entrerprise is placed in the South Last at the Goias province, especiffically at Catalão town. We priorize the aspects of the organization, administration of the work and the new projile of the employers, relating these factors to the reestruturation of the brazilian economical and political modes, result from I and II PND and statal neoliberalism that propicittad a series of privatizations, ever the enterprise mentioned above, whose consequences are seen by massa jired , outsoureinas and loses of some acquired rights by the employers.